Clinical Case of Goldenhar Syndrome in Psychiatric Practice - A. V. Kovaleva (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
A clinical case of a rare genetic oculo-auriculo-vertebral syndrome (Goldenhar syndrome) is presented in a young man of 18 years old, who was first sent for examination and treatment to the psychiatric ward. A retrospective analysis of anamnestic information indicates the emergence of psychopathological disorders in childhood in the form of a delay in psychoverbal development, emotional immaturity, and delays in the development of social behavior. Subsequently, persistent encephalasthenic and neurosis-like disorders were complicated by the addition of affective disorders of the depressive-dysphoric type and psychotic disorders. The lack of a timely integrated therapeutic approach with the addition of psychopharmacotherapy, psychotherapy and social therapy led to the formation of specific personality changes in organic etiology with significant disorders in the emotional sphere (lability of emotions, irritability, outbursts of anger, constant resentment and dissatisfaction with others), a decrease in the level of cognitive activity and a tendency to chronic course of neurosis-like and affective disorders. A statement of persistent pronounced violations of mental functions during follow-up observation caused severe restrictions in the main areas of life (communication, behavior control, education, work) and social maladaptation of the patient, which was the basis for referral to medical and social examination with the establishment of a disability group.